Only eye study 2 (OnES 2): ‘Am I going to be able to see when the patch comes off?’ A qualitative study of patient experiences of undergoing high-stakes only eye surgery - David P Crabb; Peter Shah; Deanna J Taylor; Lee Jones; Freda Sii; Imran Masood (BMJ Open)
Objectives Ocular surgery is a source of significant concern for many patients, especially in high-stakes circumstances. The purpose of this study was to explore patient experiences of undergoing surgery on their only-seeing eye.Design A qualitative investigation using semistructured face-to-face interviews. Transcripts were analysed using thematic analysis.Setting Hospital eye service in the UK.Participants Twelve participants with a diagnosis of glaucoma with worse eye visual acuity <3/60± end-stage visual field loss. All participants had experience of undergoing surgery on their better-seeing (ie, ‘only’) eye.Results Data were coded into three key themes relating to (1) emotional impact of surgery, (2) burden of visual loss and (3) coping with surgery. Patients reported depressive symptoms at all stages of their surgical journey; concern about poor visual outcomes was a common feature. Only eye surgery imposes an emotional burden due to the uncertainty regarding individuals’ ability to continue daily activities and maintaining social roles. Burden extended to the inconvenience of frequent hospital visits and difficulties with follow-up care. Participants’ ability to cope effectively with surgery appeared to be linked to extent of support from healthcare professionals. Key areas in developing trust and support were an open and transparent dialogue between surgeons and patients, continuity of care, patient inclusion in decision-making, and observable empathy.Conclusions The findings indicate a need for an enhanced model of care in only eye surgery to better target patient preferences and allay concerns inherent with these procedures.